Bodily harm - Atwood, Margaret, 1939- (Anchor Books/Doubleday, 1998)
Rennie Wilford is a journalist who writes about the latest trends and considers herself an expert on the superficial surfaces of life. When her own life takes a dark turn, she seeks to recuperate by flying to the Caribbean to research a fluffy travel piece. But her carelessly chosen destination, the tiny island of St. Antoine, is on the verge of a violent revolution and Rennie soon finds herself ensnared in a world of corruption and treachery and unsure whom to trust. By turns satiric, thrilling, and terrifying, Margaret Atwood<U+2019>s Bodily Harm charts the dark currents of the lust for power<U+2014>both sexual and political<U+2014>as it builds to a devastating climax.